2000
DOI: 10.1097/00003246-200006000-00055
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine and NG-monomethyl-l-arginine in hyperdynamic septic shock in pigs: Effects on intestinal oxygen exchange and energy balance

Abstract: Neither treatment could reverse the ETX-induced derangements of cellular energy metabolism as reflected by the increased portal venous lactate/pyruvate ratios. The NOR-induced attenuation of ileal mucosal acidosis was possibly caused by a different pattern of blood flow redistribution compared with L-NMMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Our results are in agreement with findings from rodent models done by Unno et al, who clearly demonstrated a correlation between excessive NO production and intestinal mucosal dysfunction as a result of impaired oxidative metabolism [31,32]. Blocking the excessive NO production by 1400 W alone was effective in inhibiting intestinal injury in the later phase of rat endotoxemia [8]. Finally,Tepperman et al [33] described that excessive release of nitric oxide compromises the viability of intestinal and colonic epithelial cells and directly injures the mucosa in endotoxin-challenged rats.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in agreement with findings from rodent models done by Unno et al, who clearly demonstrated a correlation between excessive NO production and intestinal mucosal dysfunction as a result of impaired oxidative metabolism [31,32]. Blocking the excessive NO production by 1400 W alone was effective in inhibiting intestinal injury in the later phase of rat endotoxemia [8]. Finally,Tepperman et al [33] described that excessive release of nitric oxide compromises the viability of intestinal and colonic epithelial cells and directly injures the mucosa in endotoxin-challenged rats.…”
Section: Discussionsupporting
confidence: 93%
“…To calculate the portal venous lactate/pyruvate ratios, both the lactate and the pyruvate concentrations were spectrophotometrically determined in duplicate as described previously [7,8,16,17]. The variation coefficients for the lactate and pyruvate measurements were 1.8% and 9.2%, respectively.…”
Section: Measurements and Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental studies (3,(12)(13)(14)(15)(16) have investigated the effects of dopamine, norepinephrine, and epinephrine on splanchnic blood flow. Differences in models, including species, fluid resuscitation, and anesthesia, make it difficult to compare these results and to extrapolate them to humans.…”
mentioning
confidence: 99%
“…During compromised mucosal tissue, the reaction mechanism has been proposed as an increase of oxygen extraction (75). However, regardless of adequate oxygen delivery, the cells are unable to use oxygen during sepsis (76). During the initiation of intestinal ischemia, whatever the cause of injury (bowel strangulation, intestinal perforation or impaired blood flow), a rise in intracellular biomarkers occurs due to the increase of intestinal permeability (77).…”
Section: Gastrointestinal Perfusion Monitoringmentioning
confidence: 99%